Handling Hyperactive Children: Game Tricks for Arranging Blocks to Make Hyperactive Children Productive - Imam Tabroni; Husnul Khotimah; Rini Purnama Sari; Ani Yuhanidz; Faizahtul Fitriyah (International Journal of Educatio Elementaria and Psychologia, 2024)
Hyperactivity in children is excessive child expression which can cause behavioral instability. Playing with blocks is an interesting and innovative learning medium to provide fun learning patterns and suppress hyperactive children's increasingly uncontrollable behaviour. This game can change the thinking power of hyperactive children into focus and fun. The research process was carried out by looking at how teachers actively use block play media to increase learning productivity according to objectives. The teacher slowly and consistently provides stages for playing with blocks, starting from those that are easy to understand to discovering new game patterns that can provide new, more functional behaviour at the stage of learning certain material. The results of the research show that varied and guided block games can change hyperactive children to follow sustainable learning patterns. Children's activities are controlled and controlled based on the learning stages determined by the teacher. The block game is also able to divert other active views to one but varied material object.